Relative docking via range-only measurements - Cao, Kun (2021)
This paper studies the problem of range-based relative docking of a single robot. In particular, we propose an integrated localization and navigation scheme for a robot to navigate itself to a desired relative displacement w.r.t. a fixed landmark at an unknown position, where the proposed controllers only require distance and odometry measurements. Instead of using a single range measurement as an indicator of the proximity to the desired docking point in existing works, the main idea of this work is to construct additional artificial anchors along the robot's motion trajectory first and then adopt the measurements corresponding to these anchors as the indicator. It is proved that the proposed controller will navigate the robot to the desired docking position asymptotically given proper parameter settings. Two simulation examples are presented to demonstrate the effectiveness of our theoretical results.